Taxonomy of the Brazilian species previously placed in Mantispa Illiger, 1798 (Neuroptera: Mantispidae), with the description of three new species - Machado, Renato José Pires; Rafael, José Albertino (Zootaxa, 2010)
Here we update the status of Brazilian Mantispidae (Neuroptera) species originally placed in the Old World genus Mantispa Illiger, 1798. We revised 15 species: Buyda phthisica (Gerstaecker, 1885), Dicromantispa debilis (Gerstaecker, 1888) (= Mantispa (Mantispilla) lineaticollis Enderlein, 1910, n. syn.), Dicromantispa gracilis (Erichson, 1839), Dicromantispa hyalina n. sp., Dicromantispa leucophaea n. sp., Dicromantispa moulti (Navás, 1909) n. comb., Dicromantispa synapsis Hoffman, 2002, Haematomantispa amazonica n. sp.; Leptomantispa ariasi (Penny, 1982) n. comb., Leptomantispa axillaris (Navás, 1908) n. comb., Leptomantispa catarinae Machado & Rafael, 2007, Leptomantispa chaos Hoffman, 2002, Leptomantispa nymphe Hoffman, 2002, Zeugomantispa compelens (Walker, 1860) (=Mantispa parvula Penny, 1982, n. syn.), Zeugomantispa virescens (Rambur, 1842). We also provide an illustrated key to subfamilies, genera and species.